Ultrafast structural changes in chiral molecules measured with free-electron lasers - P Schmidt; V Music; G Hartmann; R Boll; B Erk; S Bari; F Allum; TM Baumann; G Brenner; M Brouard; M Burt; R Coffee; et al. (IOP Publishing, 2020)
(X-ray) free-electron lasers are employed to site specifically interrogate atomic fragments during ultra-fast photolysis of chiral molecules via time-resolved photoelectron circular dichroism.